2019
DOI: 10.1002/chem.201900238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin‐Polyaniline‐Coated Pt–Ni Alloy Nanooctahedra for the Electrochemical Methanol Oxidation Reaction

Abstract: Controlling the morphology and composition of nanocatalysts constructed from metals and conductive polymers has attracted attention owing to their great potential for the development of high‐efficiency catalysts for various catalytic applications. Herein, a facile synthetic approach for ultrathin‐polyaniline‐coated Pt–Ni nanooctahedra (Pt‐Ni@PANI hybrids) with controllable PANI shell thicknesses is presented. Pt–Ni nanooctahedra/C catalysts enclosed by PANI shells with thicknesses from 0.6 to 2.4 nm were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
(82 reference statements)
0
31
0
Order By: Relevance
“…PANI with 5 nm thickness is able to embed Pt NPs on the surface of the carbon support. PANI-overcoated Pt nanocube assemblies, 66 hybrid Pd/PANI/Pd sandwich-structured nanotube arrays 67 and ultra-thin PANI-coated Pt-Ni nanooctahedra 68 have been synthesized by following a similar oxidative polymerization process. Electrochemical performance follows the change in PANI thickness; a thinner PANI layer (0.6 nm) is more beneficial for the markedly improved electrocatalytic activity towards methanol oxidation than a thicker layer.…”
Section: àmentioning
confidence: 99%
“…PANI with 5 nm thickness is able to embed Pt NPs on the surface of the carbon support. PANI-overcoated Pt nanocube assemblies, 66 hybrid Pd/PANI/Pd sandwich-structured nanotube arrays 67 and ultra-thin PANI-coated Pt-Ni nanooctahedra 68 have been synthesized by following a similar oxidative polymerization process. Electrochemical performance follows the change in PANI thickness; a thinner PANI layer (0.6 nm) is more beneficial for the markedly improved electrocatalytic activity towards methanol oxidation than a thicker layer.…”
Section: àmentioning
confidence: 99%
“…Electrooxidation of ethanol in alkaline medium proceeds via the following i) reactive intermediate and ii) poisoning intermediate pathway. [32,33] i) reactive intermediate pathway: [3,20] It has been previously reported that the up-shift of d-band center of PdÀ Pt alloy surfaces compared with that of pristine Pd surface can promote the formation of OH ads with optimal binding strength [34] and thus enhancement of EOR activity can be achieved on PdÀ Pt alloy surface due to accelerated rate of (COCH 3 ) ads oxidation. To investigate the change in the electronic structure of the PdÀ Pt alloy UANs, X-ray photoelectron spectroscopy (XPS) spectra of valence band regions were obtained and corresponding d-band center positions relative to the Fermi level were calculated.…”
Section: Full Papermentioning
confidence: 99%
“…[15][16][17][18][19] Introducing the secondary metal component can modulate the electronic structure of Pt and thus weaken the affinity of poisoning species. [20] In particular, Pd is a promising candidate to form a strong coupling with Pt and synergistically enhance the catalytic properties due to the same face-centered cubic (fcc) structure with a highly similar lattice constant of nominal mismatch of 0.77%. [6,21,22] As an another approach to enhance the electrocatalytic performance, preparing nanocrystals (NCs) can offer an advantage for increasing high accessible active sites participating in the electrocatalytic reaction due to their large surface area to volume ratio as compared with bulk materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations